Tendencje zmian przepływu rzek Polski w drugiej połowie XX wieku - Wrzesiński, Dariusz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2009)
A study was made of multi-year tendencies in monthly, seasonal and yearly series of streamflow in Poland in the second half of the 20th century. To establish changes in the time series, use was made of the non-parametric Mann-Kendall test. The analysed flow series came from 148 profiles located on 91 Polish rivers and covered 9 time intervals: two 20-year periods (1951-1970 and 1981-2000), two 25-year ones (1951-1975 and 1976-2000), two 30-year ones (1951-1980 and 1971-2000), two 40-year periods (1951-1990 and 1961-2000), and the years 1951-2000. Over the years 1951-2000, the directions of change in the series of mean monthly, seasonal and yearly streamflow in Poland were clearly different in the first and second part of this period. In all the flow series starting in 1951, upward trends decidedly prevail, being the most frequent in the years 1951 -1980. Statistically significant trends can then be observed in more than 30% of the series under analysis. Nearly 60% of the mean yearly flow series display then statistically significant growth, recorded on most of the rivers in the country except in the Mazurian Lakeland. A statistically insignificant increase in streamflow can be noted from January to April. In the remaining months the discharge figures grow markedly, although the growth varies in space and time. From May to July the discharges rise mostly on rivers in the eastern part of the country, in the Narew and Wieprz catchments, in May in the Warta catchment, and in June also in the upper Oder catchment. From August to October a significant increase in streamflow can be observed on most rivers in the country except lakeland rivers and upper reaches of the Carpathian tributaries of the Vistula. A similar distribution occurs in the remaining months, with the proportion of statistically significant trends in December dropping to 38% of the series under analysis. After 1961 the direction of variations in streamflow changes and negative trends start to predominate. The largest number of downward trends, in more than 70% of the series, although usually statistically insignificant, can be observed in the period 1971-2000. An exception is the March and April flow series when upward trends predominate. An increase in streamflow in the winter-spring season can then be observed on the rivers of the Pomeranian Lakeland (February and March) and the Carpathians (February and April). In the summer-autumn season the discharges of most rivers in this multi-year period tended to decline. Mean annual discharges on most of the studied rivers tended to grow between 1951 and 2000, but usually in a statistically insignificant way. An increase can generally be noted on rivers flowing in the eastern parts of the Vistula and Oder catchments and on coastal rivers, while a decrease, on rivers in the western parts of those catchment, not counting the upper reaches of the Sudeten tributaries of the Oder. Still, upward trends, statistically significant, are only characteristic of rivers of the Pomeranian Lakeland and locally those in the Narew catchment and some Carpathian streams. A statistically significant upward trend in the winter season on rivers in the north-east of the country, and also locally on the Sudeten and Carpathian rivers, shows that circulation factors may be responsible for the higher discharges of those rivers. This is corroborated by a diagram of isocorrelates of streamflow in those regions in the winter season with the winter NAO index, as well as differences in flows between a positive and a negative stage of this macro-scale type of circulation (WRZESIŃSKI 2008). An analysis of the spatial variability of the tendencies of change in streamflow is also made difficult by the physical-geographic conditions of the catchments and by human activity. These are elements of major importance in the shaping of flow conditions and specific features of stream regimes. The reversal observed in flow tendencies in the 1970s requires further studies to confirm the statistical significance of this change and to determine when upward trends turned into downward ones.